2017
DOI: 10.1016/j.jmb.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

abYsis: Integrated Antibody Sequence and Structure—Management, Analysis, and Prediction

Abstract: abYsis is a web-based antibody research system that includes an integrated database of antibody sequence and structure data. The system can be interrogated in numerous ways -from simple text and sequence searches to sophisticated queries that apply 3D structural constraints. The publicly available version includes pre-analysed sequence data from EMBL-ENA and Kabat as well as structure data from the PDB. A researcher's own sequences can also be analysed through the web interface.A defining characteristic of abY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 59 publications
2
151
0
Order By: Relevance
“…Structural studies of V1V2 bNAbs showed that the protruding CDRH3 is used to penetrate through the glycan shield on Env surrounding the Asn160 gp120 and Asn156 gp120 N-glycans to contact basic residues in the V2 loop (Gorman et al, 2016; McLellan et al, 2011; Pancera et al, 2013; Pan et al, 2015; Pancera et al, 2010; Pejchal et al, 2010). The BG1 CDRH3 length, 22 residues, is shorter than CDRH3 loops in other V1V2 bNAbs (Figure 1A), but longer than typical human antibody CDRH3s for which the most common length is 14 residues (Swindells et al, 2017). A 2.0 Å crystal structure of unbound BG1 Fab (Figure 1B; Table 1) revealed that, in contrast to the protruding CDRH3s in other V1V2 bNAbs, the BG1 CDRH3 does not extend notably beyond the antigen-binding site surface (Figure 1C).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Structural studies of V1V2 bNAbs showed that the protruding CDRH3 is used to penetrate through the glycan shield on Env surrounding the Asn160 gp120 and Asn156 gp120 N-glycans to contact basic residues in the V2 loop (Gorman et al, 2016; McLellan et al, 2011; Pancera et al, 2013; Pan et al, 2015; Pancera et al, 2010; Pejchal et al, 2010). The BG1 CDRH3 length, 22 residues, is shorter than CDRH3 loops in other V1V2 bNAbs (Figure 1A), but longer than typical human antibody CDRH3s for which the most common length is 14 residues (Swindells et al, 2017). A 2.0 Å crystal structure of unbound BG1 Fab (Figure 1B; Table 1) revealed that, in contrast to the protruding CDRH3s in other V1V2 bNAbs, the BG1 CDRH3 does not extend notably beyond the antigen-binding site surface (Figure 1C).…”
Section: Resultsmentioning
confidence: 83%
“…
10.7554/eLife.27389.002Figure 1.Comparison of BG1 and other V1V2 bNAbs.( A ) Sequences of the HCs of BG1 and representative other V1V2 bNAbs. Residue numbering (Kabat) refers to BG1, and the CDRs were defined using AbM (Swindells et al, 2017). ( B ) Crystal structure of BG1 Fab with highlighted CDRs.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas the CDR L1 loop of eOD01 is 15 amino acids in length, characteristic of the mouse IGKV3 germline family, the corresponding CDR L1 region of GD01 is derived from a different mouse germline group IGKV6 and is 11 amino acids (SI Appendix, Fig. S7), a length more commonly observed both in mouse and human antibodies (29) (Table 1). Interestingly, the eOD01 light-chain protein sequence shows little deviation from the germline IGKV3-2*01 V-gene (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the insertions and deletions at VDJ junctions would generate complementarity-determining region (CDR)-H3 sequences that could not be found in human antibody germline sequences, we searched for the thrombin recognition sequence in 2 additional databases: 1) a MedImmune proprietary next-generation sequencing database of over 1.4 million unique CDR-H3 sequences obtained from primary B cells from 5 healthy human donors, and 2) sequences retrieved from the abYsis database. 35 Both database searches revealed a very low frequency for the thrombin recognition sequence for the CDR-H3 (Fig. 1E).…”
Section: Imab Designmentioning
confidence: 98%
“…34 For the abYsis database, the thrombin recognition sequence was searched online using Homo sapiens as organism. 35 Sequence repertoires for the CDR-H3 were also obtained from human blood samples. One million B cells from 5 healthy donors were isolated and used to generate V H and V L amplicons that were sequenced using Illumina MiSeq 2£300 bp (SeqMagic).…”
Section: Frequency Of Thrombin Recognition Sequence In Human Antibodiesmentioning
confidence: 99%